Towards efficient use of data, models and tools in food microbiology. (August 2022) - Filter, Matthias; Nauta, Maarten; Pires, Sara M.; Guillier, Laurent; Buschhardt, Tasja
Abstract : Food microbiology researchers, risk assessment agencies and food business operators rely heavily on the reuse of knowledge that is available as data, models and tools. Unfortunately, such knowledge reuse remains challenging, as food safety data sets, models and tools are usually only available in platform-dependent or software-dependent formats that rarely comply to the Findability, Accessibility, Interoperability, and Reusability data principles. In recent years, the Risk Assessment Modelling and Knowledge Integration Platform (RAKIP) Initiative developed the so-called Food Safety Knowledge Exchange (FSKX) format. This development was accompanied by the creation of open-source software that facilitates the adoption of FSKX. Future work within RAKIP will focus on creating semantic interoperability in FSKX-related solutions and on the extension of the FSKX format towards other food microbiology knowledge. Highlights: FAIR principles and IT-based solutions will greatly influence future food systems. Interoperability of data, models and tools is an important long-term development goal. FSKX format supports exchange of food safety models and will be used in related areas. RAKIP Initiative maintains and extends FSKX-related resources.